Alternative fuels for aviation: possible alternatives and practical prospects of biofuels. Issue 1 (January 2021) - Adami, Renata; Lamberti, Patrizia; Tucci, Vincenzo; Guadagno, Liberata; Valdés, Arnaldo Rosa; Zaporozhets, Oleksandr; Wacnik, Pawel; Burmaoglu, Serhat
Abstract: The successful implementation of the new European Green Deal in aviation depends on the European aeronautics industry's ability to develop new technologies able to face the climate changes. The decarbonization in the aviation is very difficult, compared to other transport sector, and one possibility to reduce emissions is by increasing the usage of low-carbon alternative fuels. Among the analyses carried out within the Horizon 2020 project PARE – Perspectives for Aeronautical Research in Europe, one relevant aspect concerns the possible strategies already applied or under study to reach the zero-emission target using alternative fuels.